2019
DOI: 10.3390/biom9120889
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Misfolding Mechanism of Transthyretin Monomer: Insights from Hybrid-Resolution Simulations and Markov State Model Analysis

Abstract: Misfolding and aggregation of transthyretin (TTR) is widely known to be responsible for a progressive systemic disorder called amyloid transthyretin (ATTR) amyloidosis. Studies suggest that TTR aggregation is initiated by a rate-limiting dissociation of the homo-tetramer into its monomers, which can rapidly misfold and self-assemble into amyloid fibril. Thus, exploring conformational change involved in TTR monomer misfolding is of vital importance for understanding the pathogenesis of ATTR amyloidosis. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…It was previously shown that the TTR (105-115) peptide originating from the β-stand G is highly amyloidogenic (Gustavsson et al, 1991). A recent MD study reported a consistent result in which destabilization of the edge at the DAGH β-sheet, namely the β-stands D and H, is responsible for the amyloidogenic propensity of TTR (Zhou et al, 2019;Childers and Daggett, 2020). Furthermore, a series of computational studies have suggested that the DAGH β-sheet may experience structural deformation to reconstruct aggregation-prone α-sheet-like structures (Steward et al, 2008;Childers and Daggett, 2019).…”
Section: Introductionmentioning
confidence: 84%
“…It was previously shown that the TTR (105-115) peptide originating from the β-stand G is highly amyloidogenic (Gustavsson et al, 1991). A recent MD study reported a consistent result in which destabilization of the edge at the DAGH β-sheet, namely the β-stands D and H, is responsible for the amyloidogenic propensity of TTR (Zhou et al, 2019;Childers and Daggett, 2020). Furthermore, a series of computational studies have suggested that the DAGH β-sheet may experience structural deformation to reconstruct aggregation-prone α-sheet-like structures (Steward et al, 2008;Childers and Daggett, 2019).…”
Section: Introductionmentioning
confidence: 84%
“…2 , E and F ). This region has been proposed as one of the great importance through molecular dynamic studies to amyloidogenic propensity of TTR when destabilized ( 59 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Chapman–Kolmogorov (C–K) test was further performed to ensure that the constructed MSM is really Markovian. The C–K test is calculated according to the following equation: T ( n τ ) T ( τ ) n where T (τ) is the transition probability matrix with selected lag time τ and n is an integer number of steps . The C–K compares MD trajectories at increasing time steps to the probability of the protein remaining in a specific state predicted by the constructed MSM.…”
Section: Model and Methodsmentioning
confidence: 99%
“…where T(τ) is the transition probability matrix with selected lag time τ and n is an integer number of steps. 74 The C−K compares MD trajectories at increasing time steps to the probability of the protein remaining in a specific state predicted by the constructed MSM. The MSM-reweighted free energy surface (FES) along the first two PC dimensions was also computed.…”
Section: Calculation Of Fraction Of Native Contacts (Q)mentioning
confidence: 99%